Preparation method of high-capacity grafted carbon capture spherical solid amine material

By using grafting reaction and CO2 protection technology in solid amine materials, high-capacity, grafted carbon-capacitated spherical solid amine materials are prepared, which solves the stability and capture capacity of existing materials in carbon dioxide capture concentration and meets the needs of engineering applications.

CN119588323APending Publication Date: 2025-03-11CHANGZHOU ZHONGNAN CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411778663.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing solid amine materials have problems such as amine leaching, equipment corrosion and low capture capacity in carbon dioxide trapping, and the materials are mostly powdery, making it difficult to use effectively in engineering applications.

Method used

High-capacity, grafted carbon capture spherical solid amine material, and the CO2-protected polyethylene polyamine and resin are controlled under gradient heating conditions to inhibit the additional linkage of polyamines, improve the grafting rate and spatial dispersion of the polyamines, and prepare spherical granular materials.

Benefits of technology

The amine carrying capacity and carbon dioxide capture capacity of the material are significantly improved, the stability and cyclic properties of the material are ensured, and the spherical granular materials are suitable for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588323A_ABST
    Figure CN119588323A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-capacity grafted carbon capture spherical solid amine material, and the solid amine carbon capture material is prepared by taking macroporous crosslinked polystyrene containing active reaction groups as a raw material and reacting with polyethylene polyamine protected by CO2. In the gradient heating process, polyethylene polyamine protected by CO2 reacts with macroporous crosslinked polystyrene resin containing active reaction groups for grafting while being deprotected, so that an additional link reaction generated in the direct reaction process of the polyethylene polyamine and the polyethylene polyamine is avoided. The obtained solid amine carbon trapping material is granular, the amine loading capacity is obviously improved compared with that of a direct grafting method, polyethylene polyamine chains are more dispersed on the surfaces of pore channels, and thus the material has more excellent adsorption performance on carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas capture materials, and in particular relates to a high-capacity, grafted carbon capture spherical solid amine material. Background Art

[0002] With the continuous advancement of industrialization, many environmental problems caused by carbon dioxide emissions have attracted great attention. However, before the mature development of new energy and energy storage technology, fossil fuel combustion will still be the main source of energy for production and life. Therefore, it is of great significance to capture carbon dioxide from fossil fuel combustion exhaust and air.

[0003] Liquid amine absorption is currently the most widely used carbon capture technology. However, it is difficult to further promote it due to the problems of easy leaching, strong corrosiveness and high energy consumption of amines, which has aroused people's attention to solid amine alternative technology. In the solid amine preparation technology, the solid amine material obtained by simple impregnation and mixing, the amine functional component and the carrier are combined by physical action, and the stability is difficult to guarantee. There are still problems of amine leaching and equipment corrosion. On the contrary, the grafted solid amine material grafts the carrier and the amine functional component with chemical bonds, and the stability is greatly improved. However, in the process of grafting the polyamine functional component with the active carrier, it is inevitable that additional links will occur, that is, a polyamine chain reacts with multiple active groups to consume it. On the one hand, this leads to a significant reduction in the grafting rate of polyamines, and the amine content of the material is much lower than that of the solid amine material prepared by the impregnation method. On the other hand, after the additional connection, the polyamine functional group is closely attached to the surface of the carrier, which is not conducive to contact with carbon dioxide, so the carbon capture capacity is generally low. In addition, most of the existing solid amine materials are in powder form, and entrainment and other phenomena are inevitable when they come into contact with gas, which is not conducive to practical engineering applications. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a high-capacity, grafted carbon capture spherical solid amine material. The solid amine material has a higher polyamine grafting rate and the polyamine chains are more dispersed in space, so it has a higher carbon dioxide adsorption capacity; the material has good stability, and the capture capacity and quality of the material have no obvious loss after 20 cycles of adsorption-desorption; the material is in spherical granular form, which is conducive to engineering application.

[0005] The solid amine carbon capture material comprises a carrier resin particle, and a polyamine chain having a structure shown in the following formula I is grafted onto the surface of the carrier resin particle:

[0006]

[0007] In formula I, "*" represents polystyrene resin particles;

[0008] n is an integer from 1 to 250.

[0009] The method for preparing the high-capacity, grafted carbon capture solid amine material comprises the following steps:

[0010] (1) reacting a polyethylene polyamine solution with CO2 to generate a CO2-protected polyethylene polyamine;

[0011] (2) controlling the reaction of the CO2-protected polyethylene polyamine and the resin under a gradient temperature increase condition;

[0012] (3) filtering, washing, and drying the obtained resin to obtain the target material;

[0013] The invention is characterized in that the specific preparation method of the CO2 protected polyethylene polyamine in step (1) is: dissolving ethylene polyamine in a solvent, and blowing a certain amount of CO2 into the solution while stirring to generate CO2 protected polyethylene polyamine; wherein the solvent is any one of toluene, xylene, trimethylbenzene, N,N-dimethylformamide, and dioxane, or a combination of at least two thereof; the polyethylene polyamine is any one of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, PEI-600, PEI-1200, PEI-1800, and PEI-10000, or a combination of at least two thereof; the CO2 blowing speed is 50 to 250 mL / min, and the blowing time is 5 to 10 min.

[0014] The specific method of step (2) reacting the CO2-protected polyethylene polyamine with the resin is as follows: adding resin particles to the solution of the CO2-protected polyethylene polyamine obtained in step (1), controlling the temperature to gradually deprotect the CO2-protected polyethylene polyamine and reacting it with the resin particles; wherein the resin particles are chloromethylated polystyrene resins, the molar ratio of the reactive groups on the branches to the polyethylene polyamine is 1:5 to 1:40, the temperature control process is to react between 25°C and 100°C for 0.5 to 5h, and finally raise the temperature to 120°C for 12 to 24h.

[0015] The specific method of filtering, washing and drying the resin obtained in step (3) is as follows: the resin material obtained in step (2) is collected after suction filtration, washed with acid and alkali solutions, washed with water until neutral, and dried at a certain temperature to obtain the target material; wherein the acid solution is an aqueous solution of HCl with a concentration of 1 to 3M; the alkali solution is one or a combination of NaOH and KOH with a concentration of 1 to 5M; and the drying temperature is 60 to 100°C.

[0016] Compared with the prior art, the preparation method of the carbon capture solid amine material developed by the present invention effectively inhibits the additional linkage of polyamines on the resin carrier, the grafting rate of polyamines is improved and more dispersed in space, so that the amine loading and carbon dioxide capture capacity of the obtained material are greatly improved. The grafted solid amine material developed by this technology is generally stable, avoiding the problem of amine leaching, and the cyclic stability of the material is effectively guaranteed. In addition, the material is in the form of spherical particles, which is conducive to engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3.

[0018] Figure 2 This is a thermogravimetric curve of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3.

[0019] Figure 3 This is a CO2 adsorption process curve of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3.

[0020] Figure 4 This is a bar chart of CO2 cyclic adsorption of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0022] Unless otherwise specified, the raw materials involved in the specific embodiments of the present invention can be purchased from the market, and the instruments and equipment involved are conventional instruments and equipment in the field.

[0023] Example 1

[0024] A high-capacity, grafted carbon capture spherical solid amine material HAS-1, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the structure shown below are grafted:

[0025]

[0026] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-1 provided in this embodiment comprises the following steps:

[0027] (1) Take 500g of chloromethylated polystyrene resin particles (PS-CH2Cl, D 50The particle size is 0.30 mm, purchased from Jiangsu Suqing Water Treatment Engineering Group Co., Ltd.) and placed in a chromatography column. Deionized water and anhydrous ethanol are used to wash repeatedly until the effluent is clear and free of impurities. After washing, the mixture is wrapped with filter paper and dried in an oven at 65°C to constant weight.

[0028] (2) 0.68 g of ethylenediamine was placed in a 25 mL Shrek tube and dissolved in 5 mL of xylene. CO2 gas was introduced into the solution at a flow rate of 60 mL / min for 8 min. 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 乙二胺 =1:5), react at 25°C for 1h, 50°C for 2h, 75°C for 2h, and 120°C for 12h to obtain a primary product.

[0029] (3) Collect the resin product by filtration, and wash it with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then deionized water to neutrality. Wrap it with filter paper, first put it in a 65°C oven for pre-drying for 2 hours; then put it in a vacuum drying oven at 65°C and vacuum dry it to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-1.

[0030] Example 2

[0031] A high-capacity, grafted carbon capture spherical solid amine material HAS-2, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the following structure are grafted:

[0032]

[0033] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-2 provided in this embodiment comprises the following steps:

[0034] (1) Pretreatment is as in Example 1.

[0035] (2) 2.32 g of diethylenetriamine was placed in a 25 mL Shrek tube and completely dissolved in 5 mL of toluene. CO2 gas was introduced into the solution at a flow rate of 110 mL / min for 9 min. 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 二乙烯三胺 =1:10), react at 50°C for 2h, 75°C for 1h, 100°C for 2h, and 120°C for 24h to obtain the initial product.

[0036] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-2.

[0037] Example 3

[0038] A high-capacity, grafted carbon capture spherical solid amine material HAS-3, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the following structure are grafted:

[0039]

[0040] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-3 provided in this embodiment comprises the following steps:

[0041] (1) Pretreatment is as in Example 1.

[0042] (2) 4.94 g of triethylenetetramine was placed in a 25 mL Shrek tube and completely dissolved in 5 mL of trimethylbenzene. CO2 gas was introduced into the solution at a flow rate of 120 mL / min for 6 min. 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 三乙烯四胺 =1:15), react at 25°C for 1h, 50°C for 1h, 75°C for 1h, and 120°C for 12h to obtain a primary product.

[0043] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-3.

[0044] Example 4

[0045] A high-capacity, grafted carbon capture spherical solid amine material HAS-4, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the following structure are grafted:

[0046]

[0047] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-4 provided in this embodiment comprises the following steps:

[0048] (1) Pretreatment is as in Example 1.

[0049] (2) 8.52 g of tetraethylenepentamine was placed in a 25 mL Shrek tube and completely dissolved with 5 mL of N,N-dimethylformamide. CO2 gas was introduced into the solution at a flow rate of 150 mL / min for 6 min. 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 四乙烯五胺 =1:20), react at 25°C for 0.5h, 50°C for 5h, and 120°C for 24h to obtain the initial product.

[0050] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-4.

[0051] Example 5

[0052] A high-capacity, grafted carbon capture spherical solid amine material HAS-5, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the structure shown below are grafted:

[0053]

[0054] Wherein, n=14;

[0055] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-5 provided in this embodiment comprises the following steps:

[0056] (1) Pretreatment is as in Example 1.

[0057] (2) 33.75 g of PEI-600 was placed in a 50 mL Shrek tube and completely dissolved in 10 mL of toluene. CO2 gas was introduced into the solution at a flow rate of 180 mL / min for 7 min. 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-600 =1:25), react at 25°C for 1h, 50°C for 0.5h, 75°C for 2h, 100°C for 2h, and 120°C for 24h to obtain the initial product.

[0058] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-5.

[0059] Example 6

[0060] A high-capacity, grafted carbon capture spherical solid amine material HAS-6, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the following structure are grafted:

[0061]

[0062] Among them, n = 27;

[0063] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-6 provided in this embodiment comprises the following steps:

[0064] (1) Pretreatment is as in Example 1.

[0065] (2) 81.00 g of PEI-1200 was placed in a 50 mL Shrek tube and completely dissolved in 10 mL of toluene. CO2 gas was introduced into the solution at a flow rate of 200 mL / min for 8 min. 0.50 g (n=100) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-1200 =1:30), react at 75°C for 2h, 100°C for 2h, and 120°C for 12h to obtain the initial product.

[0066] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-6.

[0067] Example 7

[0068] A high-capacity, grafted carbon capture spherical solid amine material HAS-7, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the structure shown below are grafted:

[0069]

[0070] Where n = 40;

[0071] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-7 provided in this embodiment comprises the following steps:

[0072] (1) Pretreatment as in Example 1;

[0073] (2) 141.75 g of PEI-1800 was placed in a 50 mL Shrek tube and completely dissolved in 10 mL of N,N-dimethylformamide. CO2 gas was introduced into the solution at a flow rate of 220 mL / min for 8 min. 0.50 g (n=100) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-1800 =1:35), react at 25°C for 1h, 50°C for 0.5h, 75°C for 0.5h, 100°C for 2h, and 120°C for 12h to obtain a primary product.

[0074] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-7.

[0075] Example 8

[0076] A high-capacity, grafted carbon capture spherical solid amine material HAS-8, comprising polystyrene particles, on the surface of which a plurality of polyamine chains having the structure shown below are grafted:

[0077]

[0078] Where n = 225;

[0079] The preparation method of the high-capacity, grafted carbon capture spherical solid amine material HAS-8 provided in this embodiment comprises the following steps:

[0080] (1) Pretreatment as in Example 1;

[0081] (2) 225.00 g of PEI-10000 was placed in a 50 mL Shrek tube and completely dissolved with 10 mL of dioxane. CO2 gas was introduced into the solution at a flow rate of 250 mL / min for 6 min. 0.50 g (n=100) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-10000 =1:10), react at 50°C for 2h, 75°C for 2h, and 120°C for 12h to obtain the initial product.

[0082] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the high-capacity, grafted carbon capture spherical solid amine material HSA-8.

[0083] Comparative Example 1

[0084] A carbon capture solid amine material HAS-9 directly grafted with ethylenediamine, the preparation method of which comprises the following steps:

[0085] (1) Pretreatment is as in Example 1.

[0086] (2) 0.68 g of ethylenediamine was placed in a 25 mL Shrek tube and dissolved in 5 mL of xylene. 0.50 g (n=40) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 乙二胺 =1:5), react at 120°C for 24h to obtain the initial product.

[0087] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight. The directly grafted carbon capture solid amine material HSA-9 is obtained.

[0088] Comparative Example 2

[0089] A carbon capture solid amine material HAS-10 directly grafted with diethylenetriamine, the preparation method of which comprises the following steps:

[0090] (1) Pretreatment is as in Example 1.

[0091] (2) 2.32 g of diethylenetriamine was placed in a 25 mL Shrek tube and completely dissolved in 5 mL of toluene. Then, 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 二乙烯三胺 =1:10), react at 120°C for 24h to obtain the initial product.

[0092] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-10.

[0093] Comparative Example 3

[0094] A carbon capture solid amine material HAS-11 directly grafted with triethylenetetramine, the preparation method of which comprises the following steps:

[0095] (1) Pretreatment is as in Example 1.

[0096] (2) 4.94 g of triethylenetetramine was placed in a 25 mL Shrek tube and completely dissolved in 5 mL of trimethylbenzene. Then, 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 三乙烯四胺 =1:15), react at 120°C for 24h to obtain the initial product.

[0097] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-11.

[0098] Comparative Example 4

[0099] A carbon capture solid amine material HAS-12 directly grafted with tetraethylenepentamine, the preparation method of which comprises the following steps:

[0100] (1) Pretreatment is as in Example 1.

[0101] (2) 8.52 g of tetraethylenepentamine was placed in a 25 mL Shrek tube and completely dissolved in 5 mL of N,N-dimethylformamide. Then, 0.50 g (n=40) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n 四乙烯五胺 =1:20), react at 120°C for 24h to obtain the initial product.

[0102] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-12.

[0103] Comparative Example 5

[0104] A PEI-600 directly grafted carbon capture solid amine material HAS-13, the preparation method of which comprises the following steps:

[0105] (1) Pretreatment is as in Example 1.

[0106] (2) 33.75 g of PEI-600 was placed in a 50 mL Shrek tube and completely dissolved in 10 mL of toluene. Then 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-600 =1:25), react at 120°C for 24h to obtain the initial product.

[0107] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-13.

[0108] Comparative Example 6

[0109] A PEI-1200 directly grafted carbon capture solid amine material HAS-14, the preparation method of which comprises the following steps:

[0110] (1) Pretreatment is as in Example 1.

[0111] (2) 81.00 g of PEI-1200 was placed in a 50 mL Shrek tube and completely dissolved in 5 mL of toluene. Then 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-1200 =1:30), react at 120°C for 24h to obtain the initial product.

[0112] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-14.

[0113] Comparative Example 7

[0114] A PEI-1800 directly grafted carbon capture solid amine material HAS-15, the preparation method of which comprises the following steps:

[0115] (1) Pretreatment as in Example 1;

[0116] (2) Place 141.75 g of PEI-1800 in a 50 mL Shrek tube and dissolve it completely in 10 mL of N,N-dimethylformamide. Then add 0.50 g (n=100) of pretreated PS-CH2Cl to the Shrek tube. cl :n PEI-1800 =1:35), react at 120°C for 24h to obtain the initial product.

[0117] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-15.

[0118] Comparative Example 8

[0119] A PEI-10000 directly grafted carbon capture solid amine material HAS-16, the preparation method of which comprises the following steps:

[0120] (1) Pretreatment as in Example 1;

[0121] (2) 225.0 g of PEI-10000 was placed in a 50 mL Shrek tube and completely dissolved with 5 mL of dioxane. Then, 0.50 g (n=10) of pretreated PS-CH2Cl was added to the Shrek tube. cl :n PEI-10000 =1:10), react at 120°C for 24h to obtain the initial product.

[0122] (3) After the reaction is completed, the resin is collected by filtration, and washed with deionized water, anhydrous ethanol, deionized water, 1 mol / L HCl to acidity, deionized water to neutrality, 1 mol / L NaOH solution to alkalinity, and then washed with deionized water until the effluent is neutral. After wrapping with filter paper, it is first placed in a 65°C oven for pre-drying for 2 hours; then placed in a vacuum drying oven at 65°C and vacuum dried to constant weight to obtain the directly grafted carbon capture solid amine material HSA-16.

[0123] Performance Test:

[0124] Taking Example 3 as an example, the specific test method for testing the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 is as follows:

[0125] (1) Morphology test: The high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 was tested using a scanning electron microscope. The scanning electron microscope image of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 was obtained. Figure 1 shown.

[0126] from Figure 1 It can be seen that the high-capacity, grafted carbon capture solid amine material HSA-3 provided in Example 3 is spherical with a diameter of 0.6 mm and a uniform and smooth surface.

[0127] (2) Thermogravimetric test: The high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 was tested using a thermogravimetric Seteram instrument. The test conditions were: thermogravimetric testing in the range of 30-800°C, with a heating rate of 10°C / min.

[0128] from Figure 2 It can be seen that the high-capacity, grafted carbon capture spherical solid amine material HAS-3 provided in Example 3 has little mass loss before 300° C., indicating that it has strong heat resistance.

[0129] (3) CO2 adsorption performance: 30 mg of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 was weighed into an adsorption instrument, and 1 atm CO2 gas (400 sccm) was introduced at 25°C. The weight gain was recorded and the adsorption amount was calculated. The CO2 adsorption process curve of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 was obtained as shown in FIG. Figure 3 shown.

[0130] from Figure 3 It can be seen that the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 can adsorb CO2 in a CO2 atmosphere, and the adsorption amount gradually increases with the passage of time and the adsorption capacity reaches 4.24 mmol / g at 120 min.

[0131] (4) CO2 cyclic adsorption performance: 30 mg of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 was weighed into an adsorption instrument, and 1 atm CO2 gas (400 sccm) was introduced at 25°C, the weight gain was recorded, and the adsorption amount was calculated; the inlet gas was changed to N2, and the temperature was raised to 100°C for CO2 desorption for 45 min; the temperature was lowered to 25°C, the inlet gas was changed to CO2, and adsorption was performed again, and this was repeated 20 times to obtain a CO2 cyclic adsorption bar graph of the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 as shown in FIG. Figure 4 shown.

[0132] from Figure 4 It can be seen that the high-capacity, grafted carbon capture spherical solid amine material HSA-3 provided in Example 3 has strong cycle stability. After 20 adsorption / desorption cycles, the CO2 adsorption capacity of the material decreased by about 1.94%.

[0133] Although only the high-capacity, grafted carbon capture spherical solid amine material HSA-3 produced by the process of Example 3 was tested, because the other examples are high-capacity, grafted carbon capture spherical solid amine materials produced according to similar production processes, the test results should be similar thereto and will not be repeated here.

[0134] Tests on high capacity, grafted carbon capture spherical solid amine materials HSA-1 to 8 provided in Examples 1 to 8 and solid amine carbon capture materials HSA-9 to 16 provided in Comparative Examples 1 to 8

[0135] (1) Amine loading: Weigh m (about 0.1 g) of solid amine carbon capture material into a 100 mL conical flask, then transfer 50 mL of HCl solution with a concentration of C2 (about 0.10 mol / L). After shaking in a water bath at 25°C for 12 h, transfer 10 mL of the supernatant and titrate with NaOH solution with a concentration of C1 (about 0.05 mol / L) using phenolphthalein as an indicator until a slightly red color remains unfaded for 15 seconds, which is the titration endpoint. The volume of NaOH consumed is V (mL). Titrate three times in parallel according to Calculate and obtain the amine loading.

[0136] (2) CO2 adsorption capacity: Weigh about 30 mg of solid amine carbon capture material into the adsorption instrument, pass 1 atm CO2 gas at 25 °C, record the weight gain, and calculate the CO2 adsorption capacity;

[0137] (3) Amine efficiency: Amine efficiency = CO2 adsorption capacity / amine loading.

[0138] According to the above test method, the test and calculation are carried out, and the test results are shown in Table 1:

[0139] Table 1

[0140]

[0141] According to the data in Table 1, it can be seen that the high-capacity, grafted carbon capture spherical solid amine materials HSA-1 to HSA-8 provided in Examples 1 to 8 are compared one by one with the solid amine carbon capture materials HAS-9 to HAS-16 provided in Comparative Examples 1 to 8 prepared under similar conditions but without CO2 protection. The results show that: first, the amine loading of HSA-1 to HSA-8 is significantly increased, indicating that the grafting rate of polyamines on the active carrier is effectively increased by the technology of the present invention, and thus the CO2 adsorption amount is higher; secondly, the CO2 adsorption amount of amine per unit amount of substance on the HSA-1 to HSA-8 materials is increased, indicating that the polyethylene polyamine grafted by this technology is more dispersed on the material surface, thereby improving the reaction activity to CO2.

[0142] The applicant declares that the present invention illustrates a solid amine carbon capture material and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high capacity, grafted carbon capture spherical solid amine material, characterized in that: The solid amine material comprises carrier resin particles, and the surface of the carrier resin particles is grafted with a polyamine chain having a structure shown in the following formula I in a high-capacity and high-dispersion manner: In formula I, "*" represents resin particles; n is an integer from 1 to 250.

2. A method for preparing a high-capacity, grafted carbon capture spherical solid amine material as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) reacting a polyethylene polyamine solution with CO2 to generate a CO2-protected polyethylene polyamine; (2) controlling the reaction of the CO2-protected polyethylene polyamine and the resin under a gradient temperature increase condition; (3) The obtained resin is filtered, washed and dried to obtain the target material.

3. The method for preparing a high-capacity, grafted carbon capture spherical solid amine material according to claim 2, characterized in that: The specific preparation method of the CO2 protected polyethylene polyamine in step (1) is: dissolving the polyethylene polyamine in a solvent, and blowing a certain amount of CO2 into the solution while stirring to generate the CO2 protected polyethylene polyamine.

4. The method for preparing the CO2 protected polyethylene polyamine according to claim 3, characterized in that: in, The solvent is any one of toluene, xylene, trimethylbenzene, N,N-dimethylformamide, and dioxane, or a combination of at least two of them; the polyethylene polyamine is any one of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, PEI-600, PEI-1200, PEI-1800, and PEI-10000, or a combination of at least two of them; the CO2 injection speed is 50 to 250 mL / min, and the blowing time is 5 to 10 min.

5. The method for preparing a high-capacity, grafted carbon capture spherical solid amine material according to claim 2, characterized in that: The specific method of step (2) reacting the CO2 protected polyethylene polyamine with the resin is as follows: adding resin particles to the solution of the CO2 protected polyethylene polyamine obtained in step (1), controlling the temperature so that the CO2 protected polyethylene polyamine is gradually deprotected and reacted with the resin particles.

6. The specific method for reacting CO2-protected polyethylene polyamine with a resin according to claim 5, characterized in that: The resin particles are chloromethylated polystyrene resin, the molar ratio of the reactive groups on the resin to polyethylene polyamine is 1:5-1:40, the temperature control process is to react between 25°C and 100°C for 0.5-5h, and finally heat to 120°C for 12-24h.

7. The method for preparing a high-capacity, grafted spherical carbon capture solid amine material according to claim 2, characterized in that: The specific method of filtering, washing and drying the resin obtained in step (3) is as follows: the resin material obtained in step (2) is collected after suction filtration, washed with acid and alkali solutions, then washed with water until neutral, and dried at a certain temperature to obtain the target material.

8. The material washing and drying method according to claim 7, characterized in that: The acid solution is HCl aqueous solution with a concentration of 1 to 3 M; the alkali solution is one or a combination of NaOH and KOH with a concentration of 1 to 5 M; and the drying temperature is 60 to 100° C.

9. A use of the high-capacity, grafted spherical carbon capture solid amine material as claimed in claim 1, characterized in that: The applications include use in the adsorption of carbon dioxide.